(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Apetroleum refinery is an installation that manufactures finished petroleumproducts from crude oil, unfinished oils, natural gas liquids, otherhydrocarbons, and alcohol. Refined petroleum products include but are notlimited to gasolines, kerosene, distillate fuel oils (including No. 2 fuel oil),liquefied petroleum gas, asphalt, lubricating oils, diesel fuels, and residualfuels.